Gambaran Kedisiplinan Belajar Pada Siswa Kelas XI SMK Negeri 7 Semarang - Anggreni, Melliana Septi Dwi; Rakhmawati, Dini; Windaniati, Windaniati (Guidance : Jurnal Bimbingan dan Konseling, 2024)
The purpose of this research is to determine the depiction of learning discipline among 11th-grade students at SMK Negeri 7 Semarang. This research uses a descriptive quantitative approach with a survey method. The population in this research comprises all 11th-grade students at SMK Negeri 7 Semarang, totaling 612 students. The sample taken in this study consists of 191 11th-grade students. The sampling technique used is random sampling. For data collection, a Likert scale of learning discipline is used, and data analysis is conducted using SPSS 23 and Excel. Based on the research results on the "depiction of learning discipline among 11th-grade students at SMK Negeri 7 Semarang," it can be concluded that the learning discipline of 11th-grade students at SMK Negeri 7 Semarang falls into the High category, with a percentage of 59.2%, which accounts for 113 students. Meanwhile, the remaining 78 students, or 40.8%, fall into the medium category. Thus, according to the categorization obtained, the depiction of learning discipline among 11th-grade students at SMK Negeri 7 Semarang is classified as high.